LITERASI FINANCIAL DIGITAL SEBAGAI UPAYA PENINGKATAN PENGETAHUAN PEREMPUAN TERHADAP PENGEMBANGAN UMKM PADA SANGGAR BELAJAR SUNGAI BULOH MALAYSIA: Digital Financial Literacy as an Effort to Increase Women's Knowledge in Sungai Buloh, Malaysia - Anggraeni, Rasmi Nur; Rajindra, Rajindra; Mande, Henni; Akkas, Nasrulhak; Kamsur, Ahmad; Syaifullah, Muhammad Rahul (Unit Publikasi dan Jurnal Sekolah Tinggi Ilmu Ekonomi Tri Dharma Nusantara Makassar, 2024)
River Buloh, a small town in Malaysia, has great potential in the development of micro, small, and medium-sized enterprises. (UMKM). However, there is still a knowledge gap among women regarding the use of digital technology in developing their. The study aims to analyze the level of digital literacy among female UMKM owners in the Buloh River, investigate the obstacles encountered, design and implement programs to improve digital literature, as well as evaluate its impact on the development of UMKM. The research method used is a participatory action research approach (Participatory Action Research). Data was collected through surveys, interviews, and field observations. The results of the research show that the digital literacy rate of female UMKM owners in the Buloh River is still low, with the main obstacles being limited access to information, lack of training, and low confidence in adopting digital technology. The digital literacy improvement program designed and implemented in this research has proved effective in improving the knowledge and skills of women UMKM owners. The impact is seen from the increased use of digital platforms, optimization of online marketing, and better financial management. In addition, the study also formulates policy recommendations and strategies to encourage the adoption of digital technology among UMKMs managed by women in the Buloh River. The findings of this research are expected to contribute to enhancing the economic empowerment of women through the development of UMKM based on digital technology.